Islamic good governance for waqf institutions: a proposed framework - Hassan, Rusni; Mohamad Noor, Fatimah Azzahra (IGI Global, 2020)
This chapter discusses the concept of good governance in the context of Waqf institutions as a part of their process of revitalization. The study is qualitative and exploratory in nature, whereby a library research method was used by accumulating, identifying, and reviewing existing literature. Based on this information, further analysis was performed for the purpose of conceptualizing the Islamic Good Governance Framework for Waqf Institutions. However, the discussion is limited to the conceptual discussion of good governance in the context of Waqf institutions. This chapter proposes that the framework of Islamic good governance for Waqf institutions should be based on the principles of Tawhid (oneness of Allah), ‘Adalah (justice), Mas’uliyyah (accountability), Amanah (trust), Shura (mutual consultation), Taqwa (Allah-consciousness), Hisbah (enjoining virtue and avoiding evil), and Maqasid Shari’ah (objectives of Shari’ah).